Statistical correlative model in the multimodal fusion of brain images. Issue 4 (21st June 2020) - Zhang, Zhancheng; Cui, Jie; Luo, Xiaoqing; You, Qingjun
Abstract: Fusing multimodal medical images into an integrated image, providing more details and rich information thereby facilitating medical diagnosis and therapy. Most of the existing multiscale‐based fusion methods ignore the correlations between the decomposition coefficients and lead to incomplete fusion results. A novel contextual hidden Markov model (CHMM) is proposed to construct the statistical model of contourlet coefficients. First, the pair brain images are decomposed into multiscale, multidirectional, and anisotropic subbands with a contourlet transform. Then the low‐frequency components are fused with the choose‐max rule. For the high‐frequency coefficients, the CHMM is learned with the EM algorithm, and incorporate with a novel fuzzy entropy‐based context, building the fuzzy relationships among these coefficients. Finally, the fused brain image is obtained by using the inverse contourlet transform. Fusion experiments on several multimodal brain images show the superiority of the proposed method in terms of both visual quality and some widely used objective measures.